Using the Global Navigation Satellite System-Interferometric Reflectometry (GNSS-IR) technique to detect sea-level changes in Singapore : a feasibility study - Soon, Kit Ying (Nanyang Technological University, 2020)
The Global Navigation Satellite System-Interferometric Reflectometry (GNSS-IR) is an emerging sea-level monitoring technique which uses signal-to-noise ratio (SNR) analysis to provide relative sea-level measurements using GNSS signals reflected from the water surface. In several studies, it has been proven that results obtained from GNSS-IR are comparable with traditional tide gauges. However, this method has not previously been explored in Singapore’s context. In this study, which is the first of its kind in Singapore, we analyse GNSS data from two reference stations, namely Sultan Shoal (SSTS) and National Sailing Centre (SNSC). Using the data, we estimate reflector heights and relative sea-level changes. We then validate the technique by comparing the measurements to nearby tide-gauge records. The RMS difference between GNSS-IR-derived sea-level measurements and hourly tide-gauge records is found to be 8.0 cm. After validating, we use the measurements in further applications. The results were sufficient to reflect interesting findings such the different tidal regimes in the west and east of Singapore, as well as the monsoon-driven seasonal signals. This study demonstrates the feasible use of GNSS-IR to detect sea-level changes in Singapore and its considerable potential for future development.